The role of humour-based video material in facilitating an attitude shift towards water saving awareness amongst Capetonians: A qualitative exploration. - Parry, Joseph (The IIE, 2018)
This research was developed and explored through the researcher’s experience and interest in the field of using humour-based video to help shift attitudes towards social and environmental issues in Cape Town, South Africa. This provides a need to understand the dynamics of Capetonians and their response in attitude when consuming humorous video relating to the water crisis. This research project will ascertain the elements used in humour that best influence a positive shift in attitude and awareness. The literature review defines narrative theory, narrative in advertising, humour in persuasive narrative, video advertising, consumers’ attitudes and elaborates on dimensions applicable to the study. This study can provide value for South African consumers and social brands in the market by leveraging humour into their campaigns. The theoretical framework upon which this study is based is the balance theory. Semi structured interviews and questionnaires were used to conduct the research. Five participants were interviewed and their answers assisted towards solving the research problem. The findings reveal Capetonians attitudes positively shift when consuming humorous-based video. This has given insight into the effectiveness of leveraging key elements in humorous video to raise environmental awareness in Cape Town.
Keywords: Consumer behaviour; Digital technologies; Information and communication technology; Digital media; Online videos; Video advertising; Environmental awareness; Environmental campaigns